Whatsapp in the Indonesian Online EFL Learning Milieu: How Do the Students Engage? - Hidayati, Arini Nurul; Sri, Melisa; Abdullah, Fuad; Ramalia, Tenia; Yunita, Widia; Sulastri, Fera (ENGLISH FRANCA : Academic Journal of English Language and Education, 2022)
WhatsApp has been extensively used by many English as a Foreign Language (EFL) teachers in Indonesia as a near synchronous online learning platform. This program enables users to make announcements, exchange ideas and learning materials, and participate in online debates. Some recent publications inform its utilization in learning language, yet little discusses how students engage in the learning activities. Therefore, to fill this void, the present study aims to investigate the students' behavioral engagement during online learning using WhatsApp. To collect the data, this study employed observation and semi-structured interviews. An observation was completed in one class at a state university in Tasikmalaya, West Java, Indonesia to perceive how the students responded to the teacher's instructions during the learning process. Meanwhile, the interviews were conducted with nine students in a similar class. The data were analyzed using thematic analysis. The findings revealed that students engaged behaviourally by (1) posing questions or comments politely, (2) using emoticons and emojis as politeness reinforcements, and (3) confirming the unclear information behind the scene. Implications for teaching and further studies are discussed.